2014
DOI: 10.1002/ijc.29302
|View full text |Cite
|
Sign up to set email alerts
|

ATF2 contributes to cisplatin resistance in non‐small cell lung cancer and celastrol induces cisplatin resensitization through inhibition of JNK/ATF2 pathway

Abstract: ATF2 is a transcription factor involved in stress and DNA damage. A correlation between ATF2 JNK-mediated activation and resistance to damaging agents has already been reported. The purpose of the present study was to investigate whether ATF2 may have a role in acquired resistance to cisplatin in non-small cell lung cancer (NSCLC). mRNA and protein analysis on matched cancer and corresponding normal tissues from surgically resected NSCLC have been performed. Furthermore, in NSCLC cell lines, ATF2 expression le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 47 publications
(117 reference statements)
4
27
0
Order By: Relevance
“…It was previously demonstrated that protein 4.1N, a member of the protein 4.1 family, was able to suppress metastasis by inactivating JNK-c-Jun signaling pathway in NSCLC (34). Celastrol induces cisplatin re-sensitization through inhibition of the JNK/activating transcription factor 2 signaling pathway in NSCLC (35). JNK signaling mediates EPH receptor A2-dependent tumor cell proliferation, motility and cancer stem cell-like properties in NSCLC cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…It was previously demonstrated that protein 4.1N, a member of the protein 4.1 family, was able to suppress metastasis by inactivating JNK-c-Jun signaling pathway in NSCLC (34). Celastrol induces cisplatin re-sensitization through inhibition of the JNK/activating transcription factor 2 signaling pathway in NSCLC (35). JNK signaling mediates EPH receptor A2-dependent tumor cell proliferation, motility and cancer stem cell-like properties in NSCLC cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…For immunofluorescence analyses, cells were grown on glass coverslips following the procedure previously described [36], except for fixation method employed in this study, consisting in 4% paraformaldehyde/PBS. Confocal series images were taken on an inverted Zeiss LSM510 microscope equipped with a Plan-Apochromat 63X/1.4 oil immersion Ph 3 objective (Oberkochen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Each sample was quantified using spectrophotometer and 1 μg of RNA was retrotranscribed as previously described [36]. Genomic DNA contamination was removed by DNAse I treatment, according to manufacturer's protocol (Ambion, Life Technologies, Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, its anti-cancer [1114] and chemotherapy sensitization activities [15–17] were increasingly focused. However, the anti-leukemia effect of celastrol is rarely reported, especially on APL.…”
Section: Introductionmentioning
confidence: 99%